Pewarnaan Preparat Apus Tipis Malaria (Plasmodium vivax Dan Plasmodium falcifarum) Menggunakan Ekstrak Murbei Sebagai Pengganti Eosin Pada Komposisi Giemsa - Riyadi, Sandra Amalia; Fadhilah, Fitri (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2021)
Malaria is caused by the plasmodium parasite and still a threat to Indonesia. The main examination is staining of thick and thin smear preparations using Giemsa. Because giemsa is expensive, its waste is difficult to decompose, toxic and rare. Therefore, there is a need for new inventions to utilize the potential of natural components like mulberry fruit, which contains anthocyanins for coloring agents, to lessen the impact and risk of giemsa. The purpose of this study was to determine the effect of macerated ethanol extract of mulberry with a ratio of 1:3 (w/v) as an alternative to eosin in Giemsa on staining of thin blood smears of malaria, as well as knowing the best concentration in staining. This type of experimental research by observing the clarity of shape, color of parasites P.vivax, P.falcifarum, erythrocyte cells also compared with 3% giemsa as a control. This study consisted of 32 samples, 8 repetitions and 4 treatments namely P1 (3% Giemsa control), Giemsa modified mulberry eosin P2 (20%), P3 (30%), P4 (40%). The quality of the preparations was assessed based on the clarity and contrast of the colors. Kruskal-Wallis and Mann-Whitney data analysis techniques were used. The results showed that mulberry extract could be an alternative dye to replace eosin in the composition of giemsa on malaria thin smear preparations. The most effective concentration was 30% which could give the Plasmodium nuclei the same quality of staining as the control, while for the erythrocytes the staining quality was not the same as the control.